2019
DOI: 10.1002/ece3.4884
|View full text |Cite
|
Sign up to set email alerts
|

Water salinity and inundation control soil carbon decomposition during salt marsh restoration: An incubation experiment

Abstract: Coastal wetlands are a significant carbon (C) sink since they store carbon in anoxic soils. This ecosystem service is impacted by hydrologic alteration and management of these coastal habitats. Efforts to restore tidal flow to former salt marshes have increased in recent decades and are generally associated with alteration of water inundation levels and salinity. This study examined the effect of water level and salinity changes on soil organic matter decomposition during a 60‐day incubation period. Intact soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 46 publications
2
17
0
Order By: Relevance
“…Second, part of the CO 2 could dissolve in the tidal water. Also, standing water and water in pores reduces the availability of O 2 in the soil, which means an inhibition effect of heterotrophic respiration (Jimenez et al, 2012;Han et al, 2015;Wang et al, 2019a). Furthermore, we also found that tidal flooding reduced the temperature sensitivity of the nighttime ecosystem respiration (Table 2).…”
Section: The Effect Of Tides On Nee At Multiple Timescalessupporting
confidence: 54%
“…Second, part of the CO 2 could dissolve in the tidal water. Also, standing water and water in pores reduces the availability of O 2 in the soil, which means an inhibition effect of heterotrophic respiration (Jimenez et al, 2012;Han et al, 2015;Wang et al, 2019a). Furthermore, we also found that tidal flooding reduced the temperature sensitivity of the nighttime ecosystem respiration (Table 2).…”
Section: The Effect Of Tides On Nee At Multiple Timescalessupporting
confidence: 54%
“…Plant roots can also cause higher SOM decomposition rates as a consequence of increased aeration due to radial oxygen leakage (Bernal et al 2017). Prolonged soil saturation, on the other hand, slows SOM decomposition (Wang et al 2019), and increased inundation reduces soil carbon dioxide (CO 2 ) emissions (Neubauer 2013). Moreover, invertebrate detritivores may increase SOM mineralization via colonization and processing of soil and leaf litter (Scatolini & Zedler 1996; Craft 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The varied inundation conditions for seagrass (subtidal settings for leaf wrack, and within the rhizosphere for root/rhizome) compared to A. marina and C. glauca (exposed to sub-daily wetting and drying cycles on the wetland surface in the mid intertidal zone) were likely important. Less oxic conditions in the seagrass deployment would explain slower decomposition (Wang et al 2019). A lack of significant differences in composition of t 0 versus all collections other than t 729 for Z. muelleri leaves, might also be explained by our use of leaf wrack from t 0 which would have undergone some early leaching and/ or diagenesis prior to collection (Trevathan-Tackett et al 2020), thereby missing potentially significant early changes in macromolecular content and/or isotopic signatures.…”
Section: Om Composition Changes During Decompositionmentioning
confidence: 99%